Effects Of Financial Management Practices On The Operational Performance Of The Ghana Police Force - Mark Kyei; Oscar Agyemang Opoku (Pusat Publikasi Nusantara, 2023)
The study was to establish the effect of the financial management practices on the operational performance of the Ghana Police force in the Greater Accra Region of Ghana. The study used a descriptive survey design of the quantitative approach. It targeted staff of Ghana Police Service in the Greater Accra Region of Ghana. The study employed census and questionnaire was employed to gather data from them. The questionnaire was analysed descriptively using frequencies and percentages with the aid of Statistical Package for Service Solution version 26. The study found that effective financial management practices have assisted in reducing, crime apprehension and prosecution, crime rate, crime detection and prevention, protection of life and property, as well as peace and tranquility. Factors that hinder the effective financial management practices in the Ghana Police force included; political changes/interference, timeliness of resources and finance, problems of accountability and transparency, and problems of bureaucracy and inefficiency. Therefore, the study recommended that the Ghana Police Service should ensure that liquidity policy is reviewed periodically. Also, the Ghana Police Service should strengthen the system of supervision for cash collection and disbursement. Moreover, the Ghana Police Service should ensure that there is analysis of performance and plans are compared to actual plans with budget. Furthermore, the Ministry of finance in collaboration with the Ghana Police Service should release resources and finance on time. Lastly, the Ghana Police Service should ensure that there is accountability and transparency as well as reducing the bureaucracy and inefficiency